Competency Corner, Part One: Optometrists – What do we do? - Winslade, T; Winslade, N; Chou, R; Burbine, S; Hawkins, B; Ryall, L (Canadian Journal of Optometry, 2007)
In 2001 the Canadian Examiners of Optometry mandated the Competence Committee to describe the competencies required of Canadian Optometrists to provide safe and effective optometric care. The goal of this work was to provide a framework for revision of the Canadian Standard Assessment in Optometry so that questions on this exam could be directly linked to the practise-requirements of Canadian Optometrists. Work from the World Health Organization (WHO) provided an excellent foundation for the Competence Committee’s deliberations, emphasizing that Optometrists have professional responsibilities beyond providing eye and vision care. The Competence Committee followed WHO’s framework and identified four critical roles of Optometrists. These roles relate to: i. providing eye and vision care; ii. collaborating with and referring to other health care providers; iii. managing their practice, and; iv. educating within their profession. A second set of general attributes was also identified. These general attributes are needed to successfully perform the majority of the professional competencies. The Competence Committee identified five underlying general attributes: knowledge, reasoning and skills; planning and implementation; communication; values and ethics; and, selfdirected learning. The next article in this four part series provides the detailed descriptions of these professional competencies and underlying general attributes required of Canadian Optometrists.